The Reliability Level of Women's Dormitory Building Ibn Khaldun University Bogor - Lutfi, Muhamad; Chayati, Nurul; Rulhendri, Rulhendri; Aryanti, Reska; Insan, Muhammad Khaerul (ASTONJADRO, 2024)
The Ibn Khaldun University Women's Dormitory Building, Bogor (ASPIKA) is a building that functions as a temporary residence for female students. The ASPIKA Building was established 13 years ago, this has resulted in several building components and structures experiencing some damage which resulted in the function of the ASPIKA Building decreasing, so an assessment of the reliability level of the building is needed. Aspects used in the assessment of the reliability of the ASPIKA Building based on the proper function of the building include aspects of architecture, structure, utility and fire protection, accessibility, and building layout taking into account the applicable SNI standards. The method used is descriptive quantitative as well as survey data of the existing building by the Minister of Public Works No. 2/PRT/M/2006 concerning Guidelines for Building Technical Requirements. The results showed that the percentage value of the building on the architectural component aspect was 95.50%, indicating the building is in reliable condition. The percentage value on the structural component aspect of the building is 96.56%, indicating that the building is still reliable. The percentage of utility and fire protection components has a value of 65% indicating that the component aspects of the building are not reliable. Unreliable factors in utility and fire protection components are influenced by an inadequate fire prevention system so more attention must be paid to these aspects. Components in the accessibility aspect get a percentage of 65%, meaning that they are less reliable, where this value is influenced by the limited access of people with disabilities to reach areas on each floor of the building. The building layout and the environment get a 100% percentage which identifies the building layout as reliable based on the documents on the ASPIKA Building. The total value of the reliability level of ASPIKA Buildings obtained is 79.41% categorized as "Less Reliable" (reliable category is > 95%), this is influenced by the fire protection component by 65% ​​and the accessibility component by 65%. The solution that can be done by the university is to repair and procure facilities on the fire protection system and provide accessibility facilities that can make it easier for people with disabilities.